175k views
4 votes
21. 12(x + 3) = 4(2x + 9) + 4x

User Abha
by
5.3k points

2 Answers

5 votes

4(2x + 9) +4x = 21.12(x + 3)

Simplify left side

8x + 36 + 4x = 21.12( x + 3)

Add 8x and 4x

12x + 36 = 21.12(x + 3)

Simplify 21.12(x + 3)

12x + 36 = 21.12x + 63.36

Move all terms containing x to left side of the equation

-9.12x + 36 = 63.36

-9.12x = 27.36

Divide each terms by -9.12 and simplify

x = -3 final answer

User Grayda
by
5.2k points
2 votes

Answer:

Explanation:

12x+36 =8x+36+4x

12x+36= 12x+36

which means any value of x will work.

User Strawberry Farmer
by
5.1k points